Effects of Refined Petroleum Product (Kerosene) Flame and Fumes on the Performance of Broiler Chickens - Amakiri, A.O.; Owen, O.J.; Iboh, I.I. (International Journal of Poultry Science, 2009)
An investigation was carried out to evaluate the effects of refined petroleum product (kerosene) flame on body weight gains, feed intake, feed conversion, mortality and internal organ weights (liver, lungs, kidney and heart) of broiler chickens. One hundred and twenty day old broiler birds (Aboika breed) were randomly assigned to 4 treatment groups of 30 birds per treatment, replicated thrice with 10 birds per replicate using Completely Randomized Design (CRD). Kerosene flame in a designed burner was placed 4, 8 and 12 metres from the birds respectively, which represented treatments 1, 2 and 3 while treatment 4 was in another poultry house without flame. The birds were fed ad-libitum on a proprietary starters mash for 5 weeks and a broiler finisher mash for 3 weeks. Water was provided ad-libitum. Routine inoculations and other medications were administered when due. Burning was from 6.00 am-10.00 pm daily for 56 days. Results indicated that the distances (treatments) did not significantly (p>0.05) affect mortality and organ weights. However, the flame distance significantly (p